2014
DOI: 10.1039/c4ta04277h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of symmetric supercapacitors based on MOF-derived nanoporous carbons

Abstract: Nanoporous carbon (NPC) materials with high specific surface area have attracted considerable attention for electrochemical energy storage applications. In the present work, we have designed novel symmetric supercapacitors based on NPC by direct carbonization of Zn-based metal-organic frameworks (MOFs) without using an additional precursor. By controlling the reaction conditions in the present study, we synthesized NPC with two different particle sizes. The effects of particle size and mass loadings on superca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(169 citation statements)
references
References 47 publications
3
162
0
Order By: Relevance
“…For example, they have been used as supercapacitor [3][4][5], catalyst support [6][7][8] and adsorbent for hydrogen storage [9] as well as CO 2 capture [2,[10][11][12]. In particular, they are widely used as adsorbents to remove organic and heavy metal contaminants from water in water treatment and purification [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, they have been used as supercapacitor [3][4][5], catalyst support [6][7][8] and adsorbent for hydrogen storage [9] as well as CO 2 capture [2,[10][11][12]. In particular, they are widely used as adsorbents to remove organic and heavy metal contaminants from water in water treatment and purification [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, unlike direct carbonizs MOF-5, all the samples show type-I isotherm in nitrogen sorption tests and have a sharp distribution at the pore width of 10.6 Å (Figure 3), which is close to the pore size of ZIF-8 (12.5 Å). [66] Other samples prepared by direct carbonization of ZIF-8 generally attain higher levels of porosity, [71][72][73][74][75] especially for the PCP (Table 6, No. 9) obtained by calcining ZIF-8 at 1000 ℃ for 8 h which has BET surface area as high as 1980 m 2 /g, meanwhile, the pore size distribution keeps concentrated at 1.8 and 3.6 nm.…”
Section: Non-metal Doped Porous Carbonmentioning
confidence: 99%
“…The influences of particle size on electrochemical performances were thoroughly investigated. The large-size NPC showed a higher capacitance value of 251 F g −1 at 5 mV s −1 scan rate than that of small-size NPC due to the fact that particle aggregation and strong interaction between the fine particles limited the ability of the electrolyte to diffuse inside the deep pore surfaces [53]. In addition, the effect of carbonization temperatures (from 700 to 1000°C) on ZIF-8 precursor was also evaluated by Yamauchi et al The results indicated that the S-900 (carbonization at 900°C) achieved the highest capacitance performance in aqueous electrolytes [178].…”
Section: Metal-organic Framework-derived Carbonmentioning
confidence: 99%
“…Carbon materials are proposed as the best candidates for energy storage owing to the attractive advantages including natural abundance, easy availability, low cost, eco-friendliness, and stability. Hitherto, different dimensional (0D, 1D, 2D, 3D) carbon materials, such as carbon onions (0D) [8,[12][13][14][15], carbon nanospheres (0D) [16][17][18][19][20], carbon fibers (1D) [21][22][23][24][25][26], carbon nanotubes (1D) [27][28][29], graphenes/ graphene oxide (2D) [30][31][32][33][34][35], carbon nanosheets (2D) [36][37][38][39], hierarchically porous carbons (3D) [40][41][42][43][44], carbide-derived carbons (3D) [45][46][47][48], templated carbons (3D) [49][50][51][52], metal-organic framework (MOF)-derived carbon (3D) [53][54][55][56][57][58][59], and carbon aerogels (3D) [60][61][62]<...>…”
Section: Introductionmentioning
confidence: 99%